2022
DOI: 10.1029/2021jd036385
|View full text |Cite
|
Sign up to set email alerts
|

NOx and O3 Trends at U.S. Non‐Attainment Areas for 1995–2020: Influence of COVID‐19 Reductions and Wildland Fires on Policy‐Relevant Concentrations

Abstract: Surface ozone (O 3 ) is formed from photochemical reactions of nitrogen oxides (NO x = NO + NO 2 ) and volatile organic compounds (VOCs). O 3 has serious health impacts up to and including premature mortality (Bell et al., 2004;Di et al., 2017). In the U.S., reductions in NO x and VOCs over the past several decades have reduced peak O 3 concentrations considerably (Simon et al., 2015), but at present, there are still more than 100 million Americans living in areas that do not meet the O 3 standard (American Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
(112 reference statements)
2
6
0
Order By: Relevance
“…An attribution study of this free tropospheric enhancement has not yet been conducted. A previous study found strong correlation between enhanced ozone and fires for 2017, 2018, and 2020 in urban areas over WNA (Jaffe et al., 2022), and we suggest that a future attribution study could explore the possibility that wildfire smoke impacted free tropospheric ozone.…”
Section: Results: Trend Detection Of Free Tropospheric Ozone Based On...supporting
confidence: 53%
See 3 more Smart Citations
“…An attribution study of this free tropospheric enhancement has not yet been conducted. A previous study found strong correlation between enhanced ozone and fires for 2017, 2018, and 2020 in urban areas over WNA (Jaffe et al., 2022), and we suggest that a future attribution study could explore the possibility that wildfire smoke impacted free tropospheric ozone.…”
Section: Results: Trend Detection Of Free Tropospheric Ozone Based On...supporting
confidence: 53%
“…When we limit the study period to a shorter time frame (2004-2021), similar seasonal patterns can still be observed. Consistent positive trends can be observed at MBO, with much stronger enhancements in August-October presumably due to the wildfire impacts (Baylon et al, 2015;Jaffe et al, 2022;Laing et al, 2016). A better agreement of trends between MBO and the free troposphere above WNA/California is observed in April-July.…”
Section: Summary Of Differences In Trends Between the Free Tropospher...supporting
confidence: 63%
See 2 more Smart Citations
“…To meet this standard, the three year average of the annual fourth-highest maximum daily 8 h average (MDA8) O 3 concentration cannot exceed 70 ppb. The successes and challenges that different regions of the U.S. have experienced when trying to comply with the national O 3 standard have been well-documented. Since O 3 has significant health and regulatory implications at high concentrations, it is essential to understand the chemical and meteorological factors impacting O 3 levels.…”
Section: Introductionmentioning
confidence: 99%